2019
DOI: 10.1155/2019/9782373
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Alleviate DHEA-Induced Polycystic Ovary Syndrome (PCOS) by Inhibiting Inflammation in Mice

Abstract: Polycystic ovary syndrome (PCOS) is the most common cause of anovulatory infertility in women of reproductive age. Chronic inflammation is considered to be the cause of ovarian dysfunction. Increasing evidence in animal studies and in preliminary clinical trials has demonstrated that MSCs possess immunomodulatory effects via their interaction with immune cells. However, their contribution to PCOS remains unclear. In this study, we showed that the administration of hUC-MSCs could efficiently improve the patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…These effects seem to be related to pathways that induce regeneration and angiogenesis, which may also improve ovarian function. This potential mechanism of MSCs activity is of particular importance since these pathways can regulate immune responses and inflammation, improve injured tissues, and stimulate progenitor cells to different iate into specific-tissue cells (5,30). Here, review studies of the biology and clinical utility of MSCs from several different sources to treat female reproductive system disorders (Table 1).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects seem to be related to pathways that induce regeneration and angiogenesis, which may also improve ovarian function. This potential mechanism of MSCs activity is of particular importance since these pathways can regulate immune responses and inflammation, improve injured tissues, and stimulate progenitor cells to different iate into specific-tissue cells (5,30). Here, review studies of the biology and clinical utility of MSCs from several different sources to treat female reproductive system disorders (Table 1).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Researchers found that UC-MSC transplantation restored ovarian function in dehydroepiandrosterone (DHEA)-induced PCOS in mice. This effect was mediated by downregulation of inflammatory cytokine expression, including interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and interferon gamma (IFN-γ), as well as fibrosis-related genes such as connective tissue growth factor (CTGF) (30). While these studies suggest that UC-MSC transplantation may be helpful for controlling disorders related to the ovaries, more studies are needed to develop a valid US-MSC-based therapeutic approach.…”
Section: Umbilical Cord Mesenchymal Stem Cells (Uc-mentioning
confidence: 99%
“…These effects seem to be related to pathways that induce regeneration and angiogenesis, which may also improve ovarian function. This potential mechanism of MSCs activity is of particular importance, since these pathways can regulate immune responses and inflammation, improve injured tissues, and stimulate progenitor cells to differentiate into specific tissue cells [ 5 , 36 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Researchers found that UC-MSC transplantation restored ovarian function in dehydroepiandrosterone (DHEA)-induced PCOS in mice. This effect was mediated by the downregulation of inflammatory cytokine expression, including interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and interferon gamma (IFN-γ), as well as fibrosis-related genes such as connective tissue growth factor (CTGF) [ 36 ]. While these studies suggest that UC-MSC transplantation may be helpful for controlling disorders related to the ovaries, more studies are needed to develop a valid US-MSC‒based therapeutic approach.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…AGE-RAGE signalling may activate multiple intracellular signalling pathways involving protein kinase C and MAPKs and may influence NF-κB activity. Research has shown an association between PCOS and chronic inflammatory factors, proinflammatory cytokines such as interleukin-1, interleukin-6, interleukin-17 [41][42][43], and tumour necrosis-α, and a variety of inflammationrelated genes, including VEGF, tissue factor, and RAGE [44,45].…”
mentioning
confidence: 99%